(3eSfO GdEeGe CMeO Hf MfHds - (3GdTjHGfj, GdeQhRj, GdHZOGOj, CHh YHO Gddg, CMeO Hf eMeO Hf MfHd, J (B241(3g`s
(3ChdgG (B:s
(3Cf dG jQeheQYI GdYbHI MJi JWdY GdTeS MOKfG YHO Gddg CHj KfG CSHGW , KfG CHh ESMGb jYfj GdTjHGfj , Yf jRjO Hf GdCUe , bGd (B: (3CJjJ GHf YHGS , abdJ (B: (3JRhL adGfG (B( (3cPG (B) (3, abQH EdjfG WYGeG , aCcdfGs
(3BNQgG (B:s
(3KfG YHO Gddg MOKfj CHj KfG CHh YGeQ , KfG gTGe , jYfj GHf SYO , Yf SYjO Hf CHj gdGd , Yf QHjYI Hf Sja , Yf YHO Gddg Hf YeQh , Yf GdfHj Udi Gddg Ydjg hSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 203s
(3eYLe GdeDdajf (B1 / 261s
(3cTa GdXfhf (B2 / 1680s
(3JGQjN GdESdGe (B/ (3hajGJ (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs